Proteins as nanocarriers to regulate parenteral delivery of tramadol - Agrawal, Shubhang; Patel, Pratikshkumar R.; Gundloori, Rathna Venkata Naga (ACS Omega, 2019)
Tramadol (Td) is a centrally acting opioid analgesic drug used for the treatment of moderate to severe pain. However, the half-life of Td is about 6-8 h, which is a major drawback. To increase the half-life of Td, it needs to be entrapped in a suitable substrate with the capability to release the drug for an extended period of time. Accordingly, in our studies, new protein blends in various compositions were prepared using hydrophilic (egg albumin) and hydrophobic (zein) proteins and fabricated them as nanoparticles with Td by the desolvation method. The prepared nanoparticles were characterized using analytical techniques. The morphology and diameter of the nanoparticles were determined by an environmental scanning electron microscope. The interactions between Td and proteins were confirmed by fluorescence spectroscopy, and the secondary structural changes were evaluated by circular dichroism. The hemolysis test and MTT assay indicated that the nanoparticles were nontoxic, and drug release studies showed an extended duration of release of Td for more than 48 h. The mechanism of the drug release followed the zero order. The overall studies inferred that these protein based nanoparticles have potential to release Td at a slow rate for an extended period of time. Further manipulation of the protein composition may regulate the duration of Td release for an effective therapy.